A case of rheumatoid arthritis with features of systemic lupus erythematosus - Kumar, Deepak; Debnath, Abhinaba (International Journal of Research in Medical Sciences, 2016)
A 50 year old female presented with features qualifying for both rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Patient fulfilled 10/10 ACR-EULAR criteria for RA, her anti-CCP was positive (21.6 RU/ml), her DAS28 score was 7.55 (favouring RA) and she fulfilled ≥4 of 11 criteria’s of SLE (definite SLE). Coexistence of SLE and RA is known as “rhupus”. The immunopathological process of SLE and RA are considered to be exact opposite of one another so their coexistence remains one of the debated topics of rheumatology.